Effects of ATX-MS-1467 immunotherapy over 16 weeks in relapsing multiple sclerosis. (13th March 2018) - Chataway, Jeremy; Martin, Keith; Barrell, Kevin; Sharrack, Basil; Stolt, Pelle; Wraith, David C.
Abstract : Objective: To assess safety, tolerability, and efficacy of the antigen-specific immunotherapy ATX-MS-1467 in participants with relapsing multiple sclerosis using different treatment protocols to induce tolerance. Methods: Two open-label trials in adult participants with relapsing multiple sclerosis were conducted. Study 1 was a multicenter, phase 1b safety evaluation comparing intradermal (i.d.) (cohort 1) with subcutaneous (cohort 2) administration in 43 participants. Both cohorts received ATX-MS-1467 dosed at 25, 50, 100, 400, and 800 μg at 14-day intervals over 8 weeks, followed by 8 weeks with 4 additional 800-μg doses at 14-day intervals and 32 weeks off study medication. Study 2 was a phase 2a, multicenter, single-arm trial enrolling 37 participants. ATX-MS-1467 was titrated from 50 μg i.d. on day 1 to 200 μg on day 15 and 800 μg on day 29 followed by biweekly administration of 800 μg for 16 weeks and 16 weeks off study medication. Efficacy was evaluated on MRI parameters and clinical variables. Safety endpoints included treatment-emergent adverse events and injection-site reactions. Results: In study 1, there was a significant decrease in new/persisting T1 gadolinium-enhanced (GdE) lesions in cohort 1 from baseline to week 16, returning to baseline values at week 48. In study 2, the number of T1 GdE lesions were significantly reduced on treatment and remained reduced at study completion. Safety results were unremarkable in both studies. Conclusion: Relatively slow ATX-MS-1467 titration and a longer full-dose i.d. treatment period is associated with reduction in GdE lesions and a sustained effect post treatment. Further trials of ATX-MS-1467 are warranted. Classification of evidence: This work provides Class IV evidence that for patients with relapsing multiple sclerosis, slow ATX-MS-1467 titration and a longer full-dose i.d. treatment period is associated with reduction in GdE lesions.